10 year anniversary. (27th February 2019) - Grant, Maria J.
Abstract : Maria Grant reflects on her ten years as Editor‐in‐Chief of the Health Information and Libraries Journal, her vision to enhance the quality and reach of the journal, and working with prospective authors in the health library sector to increase confidence in recognising and communicating the value of the work being undertaken.